Deciphering Local Microstrain-Induced Optimization of Asymmetric Fe Single Atomic Sites for Efficient Oxygen Reduction - Peng Zhang; Siying Huang; Kuo Chen; Xiaoqi Liu; Yachao Xu; Yongming Chai; Yunqi Liu; Yuan Pan (Nano-Micro Letters)
Highlights Crucial role of local microstrain was deciphered to boost oxygen electrocatalysis via quantitatively riveting asymmetric Fe–N3S1 sites on carbon hollow nanospheres with specific curvature. The local microstrain accelerates kinetics of *OH reduction on Fe–N3S1, enabling much enhanced intrinsic activity, selectivity and stability toward oxygen electrocatalysis. The strained Fe–N3S1 sites were monitored to transformed into Fe–N3–S1 sites, further dynamically mitigating the overadsorption of *OH intermediates.